Measurements for stresses in machine components - IAkovlev, V. F. (Vsevolod Fedorovich); Iniutin, I. S. (Ivan Sergeevich) (Pergamon Press; [distributed in the Western Hemisphere by Macmillan, New York], 1964)
Measurements for Stresses in Machine Components focuses on the state of stress and strain of components and members, which determines the service life and strength of machines and structures.